Perbandingan Motivasi Belajar Siswa IPA dan IPS Pada Pembelajaran Daring dan Luring di SMAN 1 Kec. Akabiluru - Tiwi Purnama Sari; Ike Sylvia (Universitas Negeri Padang, 2022)
This research is motivated by the existence of a learning system that is carried out online and offline which causes science and social studies students not to be enthusiastic in participating in the learning process. The motivation that each student has in participating in learning is different, because there are many factors that can affect student learning motivation. Therefore, this research was conducted with the aim of knowing the learning motivation of science and social studies students in online and offline learning and the comparison of the two. This type of research is ex post facto with a comparative method. The population in this study were students of class XI IPA 2 and XI IPS 2 at SMAN 1 Kec. Akabiluru, in the teaching of July-December 2021/2022. The number of samples in this study were 60 students. The data used is the type of primary data obtained by distributing questionnaires to students in class XI IPA 2 and XI IPS 2 at SMAN 1 Kec. Akabiluru. The analytical method used is hypothesis testing using SPSS version 26 Analyze Frequencies. The results showed that the results of the independent sample T-Test obtained results of 0.00 <0.05 which means that there is a significant comparison of learning motivation between students XI IPA 2 and XI IPS 2 at SMAN 1 Kec. Akabiluru. These differences are influenced by (1) the desire and desire to succeed, (2) the drive and need for learning, (3) and the hopes and aspirations for the future.